2017
DOI: 10.1111/ijcp.12926
|View full text |Cite
|
Sign up to set email alerts
|

Italian patients with more recent onset of Major Depressive Disorder have a shorter duration of untreated illness

Abstract: Our findings indicate a significant DUI reduction in MDD patients whose onset occurred after vs before 2000, along with other relevant differences in terms of onset-related correlates and first pharmacotherapy. Further studies with larger samples are warranted to confirm the present findings in Italy and other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The mean DUI in our sample was 77.2 ± 103.0 months and was significantly longer for BD‐II, compared to BD‐I, BD‐NOS and cyclothymia patients. In previous studies by our group (Altamura et al, 2007, 2015), we reported a mean DUI around 80 months in BD patients, with some data suggesting a reduction in DUI over time in recent years (Dell'sso et al, 2017). Confirming the potential risk of mistreatment and delayed treatment in BD patients with ADs at onset, the DUI was significantly longer in A+ vs A− patients in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…The mean DUI in our sample was 77.2 ± 103.0 months and was significantly longer for BD‐II, compared to BD‐I, BD‐NOS and cyclothymia patients. In previous studies by our group (Altamura et al, 2007, 2015), we reported a mean DUI around 80 months in BD patients, with some data suggesting a reduction in DUI over time in recent years (Dell'sso et al, 2017). Confirming the potential risk of mistreatment and delayed treatment in BD patients with ADs at onset, the DUI was significantly longer in A+ vs A− patients in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…74 what is of interest is that there was even a signi cant decrease in DUI in the major depressive disorder groups whose onset occurred prior to the last century vs,as reported in an Italy study. 75 larger samples in different regions and time periods with targeted cognitive questionnaire and are warranted to con rm these results in DUI in further studies…”
Section: Duration Of Untreated Diseasementioning
confidence: 73%
“…Furthermore, the mean duration of illness in this study (25.00 months) was longer than those of previous studies (mean = 0.7 years). Previous studies have also indicated that duration of illness can affect adverse consequences in terms of outcome for individuals with MDD (47). Therefore, it is reasonable to assume that these inconsistencies in results are due to differences in age of subjects and the duration of their illness.…”
Section: Discussionmentioning
confidence: 99%